Expression of SOX2OT, DANCR and TINCR long non‑coding RNAs in papillary thyroid cancer and its effects on clinicopathological features - Icduygu, Fadime Mutlu; Akgun, Egemen; Sengul, Demet; Ozgoz, Asuman; Alp, Ebru (Spandidos Publications, 2022)
Long non‑coding RNAs (lncRNAs) are molecules that are >200 base pairs long and do not encode a protein. However, they perform important roles in regulating gene expression. Recent studies have revealed that the changes in the expressions of lncRNAs serve a role in the development and metastases of a number of types of cancer. A number of studies have been published on the association of SOX2 overlapping transcript (SOX2OT), differentiation antagonizing non‑protein coding RNA (DANCR) and tissue differentiation‑induced non‑coding RNA (TINCR) expression with various types of cancer. However, researchers have not yet studied their roles in papillary thyroid cancer or at least, those roles are not clarified. The aim of the present study was to investigate the expression and clinical significance of SOX2OT, DANCR and TINCR in papillary thyroid cancer (PTC). A total of 102 patients with PTC were included in the present study. Reverse transcription‑quantitative PCR method was used to determine the relative gene expression levels of lncRNAs and then the relationship between expressions of lncRNAs and clinical characteristics of the subjects was analyzed in detail. Expression levels of SOX2OT (P=0.016) and DANCR (P=0.017) increased in the tumor samples in contrast to the normal tissues. No significant difference was observed in the expression level of TINCR (P=0.298). In addition, SOX2OT expression was associated with micro carcinoma (P<0.001), tumor size (P=0.010) and primary tumor (P=0.006), while DANCR expression was associated with age (P=0.030) and micro carcinoma (P=0.004). The findings of the present study indicated that DANCR may contribute to the development of PTC while SOX2OT may contribute to both the development and progression of PTC.
Keywords: Adult; Gene Expression Regulation, Neoplastic; Male; Thyroid Cancer, Papillary; Humans; Female; RNA, Long Noncoding; Articles; Thyroid Neoplasms; Middle Aged